Distant somatic hybridization alters the structure of wheat root bacterial microbiota. (6th January 2022) - Yang, Zhengting; Chen, Xiaoyan; Huang, Yufeng; Song, Jiawang; Shi, Tianlong; Li, Yuke; Tang, Xiaoxin; Yi, Yin; Li, Fei
Abstract: Root microbiota affect the host plant's adaptation to adverse environments. The structure and function of plant root bacterial communities are affected by soil physicochemical properties and plant genotypes. Distant hybridization is a common breeding strategy to introgress the excellent genes of wild relatives into the crop genome. The effect of distant hybridization on the crop root microbiota has not been reported. In this study, the structure and function of root bacterial community of the somatic hybrid wheat introgression lines SR3 and SR4, which have been respectively reported to be tolerant to salt and saline‐alkali stress, and their parent wheat cultivar JN177 as well as common wheat cultivar Chinese Spring (CS) were analyzed using 16S rRNA high‐throughput sequencing technology. The results showed that distant hybridization altered the structure and function of wheat ( Triticum aestivum L.) root bacterial community. Compared with the parent JN177, some bacterial genera related to plant growth and stress resistance showed higher abundance in SR3 and SR4. Intriguingly, compared with parent JN177, the root bacterial communities of SR3 and SR4 are more similar to that of CS. This indicated that the process of distant hybridization may alter key genes regulating wheat root microbiota. Core Ideas: Distant somatic hybridization altered the structure of wheat root bacterial community. Bacterial genera related to stress resistance showed higher abundance in wheat introgression lines. The process of distant somatic hybridization may alter key genes regulating wheat root microbiota. Distant somatic hybridization alters the structure of wheat root bacterial microbiota.